Analysis of Dust Storms Using Satellite Imagery and Surface Observation on Iraq - Hussain Zaydan Ali; Saad H. Farraj; Sadeq A. Rashid (Journal of Madenat Alelem University College, 2013)
In most areas in Iraq, dust storms can be classified by the prevailed broad meteorological conditions. Examining the most common events that occurred in Iraq is important, specially the dust storms which caused by prefrontal and postfrontal winds that primarily occurred in the winter, and dust storms caused by persistent northerlies upon which occurred in summer. The objectives of this paper is concentrated on analyzing the synoptic situation leading up to such event south of Iraq and to conduct a complete case study of the meteorological conditions that led to the dust storm. The case study has been included an analysis of the lower level that will be used to assess the placement and timing of the surface cold front and the associated strong winds which lifted the dust. These analyses will be compared with the satellite imagery.